Single-cell transcriptome sequencing reveals the cell populations and functions associated with stony coral Pocillopora damicornis - Diao, Wenguang; Zhang, Shengyao; Zhu, Xueying; Wu, Peiqi; Du, Bingyan; Han, Zhe; Liu, Yunqing; He, Chunpeng; Lu, Zuhong (Frontiers in Marine Science, 2025)
Introduction: Pocillopora damicornis, a key species of stony corals, has been the subject of considerable scientific study. However, the cellular composition of P. damicornis and the roles of these cells in endosymbiosis and biomineralization remain elusive. The development of single-cell technology has provided new opportunities for researching the cellular and molecular mechanisms underlying symbiosis and mineralization. Nevertheless, the stringent environmental requirements, the complexity of the cellular components, and the paucity of high-quality reference genomes of P. damicornis have posed significant challenges for single-cell transcriptome research.